Improved Maize Varieties and Poverty in Rural Ethiopia - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2014)
his Impact Brief (No 45) is based on the study that documents the impacts of improved maize varities on household well-being and on overall rural poverty using primary data. In Ethiopia, the last four decades have seen more than 40 improved varieties of maize - including hybrids and OPVs – developed and released by the Ethiopian Institute of Agricultural Research (EIAR) in collaboration with the International Maize and Wheat Improvement Center (CIMMYT). The full report will be published shortly on this site along with the SPIA foreword. The journal paper (Agricultural Economics) is available on Wiley Online Library (http://onlinelibrary.wiley.com/doi/10.1111/agec.12178/abstract?campaign=wolearlyview)